Financial Governance and Logistics in Re-Election: Case Study of the 2020 Labuhanbatu Regency KPU - Panjaitan, Syaiful Rahman; Amin, Muryanto; Situmorang, Tonny P. (PERSPEKTIF, 2024)
This research delves into the financial and logistical management practices employed by the General Election Commission (KPU) of Labuhanbatu Regency during the 2020 Regent and Deputy Regent elections, with a particular focus on the subsequent re-voting processes. Following elections, it's common for unsuccessful candidates to contest results, leading to legal challenges and, in some cases, re-voting. Labuhanbatu Regency's experience is noteworthy as it underwent re-voting twice. Utilizing a qualitative research approach with a descriptive framework, this study reveals that the financial and logistical governance by the Labuhanbatu KPU was effectively executed, ensuring smooth re-voting procedures, minimizing the likelihood of errors, and bolstering public trust in democratic processes. Recommendations stemming from this research advocate for the recruitment of polling station (TPS) officers based on merit and experience to enhance service quality. Moreover, it underscores the importance of sustaining effective financial and logistical management practices to preempt future re-voting scenarios, even in the absence of significant hurdles.